2006
DOI: 10.1590/s0100-204x2006000200014
|View full text |Cite
|
Sign up to set email alerts
|

Resposta do dendezeiro à adição de nitrogênio e sua influência na população de bactérias diazotróficas

Abstract: Resumo -O dendê (Elaeis guineensis, Jaquim) pode produzir até sete toneladas de óleo por hectare por ano. O óleo vegetal é muito versátil e pode ser usado desde a indústria alimentícia até a produção de biocombustíveis. A planta é capaz de se associar com bactérias diazotróficas que colonizam raízes e caules. O objetivo deste trabalho foi avaliar a resposta à adubação nitrogenada de 17 genótipos de dendê no primeiro ano de cultivo e avaliar a influência da adição do N mineral sobre a população de bactérias dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 8 publications
0
10
0
2
Order By: Relevance
“…As there was no appropriate reference plant used in either trial, it would be premature to describe any of the oil palm ecotypes as unable to obtain N from BNF. Moreover, diazotrophic bacteria were verified in leaves and roots of all of the ecotypes (Carvalho et al 2006), which is strongly indicative that any of the ecotypes could be candidates as "N 2 -fixers".…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…As there was no appropriate reference plant used in either trial, it would be premature to describe any of the oil palm ecotypes as unable to obtain N from BNF. Moreover, diazotrophic bacteria were verified in leaves and roots of all of the ecotypes (Carvalho et al 2006), which is strongly indicative that any of the ecotypes could be candidates as "N 2 -fixers".…”
Section: Discussionmentioning
confidence: 78%
“…More recently, Carvalho et al (2006) found no differences in population of diazotrophic bacteria isolated from leaves and roots of oil palm plants grown in soil with or without N-fertiliser application. However, N fertilised plants developed much better than the non-fertilised ones, suggesting that BNF can not provide all the N needs for optimal plant growth.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…African oil palm has grown an importance, being the second highest cultivation worldwide, contributing to the mitigation of greenhouse effect [36].…”
Section: Dendê (Palm Oil In English) Cultivationmentioning
confidence: 99%
“…Its plantation in degraded areas helps to recover the vegetation of deforested area and offers an alternative place (instead of deforesting another area to cultivation fixation). According to Carvalho et al [36], in Brazil, Amazon has 70 million hectares appropriate for cultivating palm oil: 50 million in the state of Amazonas and 20 million in the state of Pará. Planting in these areas may convert the country into one of the hugest worldwide producer, with relevance to ecologic and energetic scenery.…”
Section: Utilization Of Deforested Areas At the Brazilian Amazonmentioning
confidence: 99%